Peran Green Brand Image dan Green Product dalam Membangun Loyalitas Konsumen Avoskin melalui Green Trust - Herlina Kusuma Wardhani; Sudarmiatin Sudarmiatin; Wening Patmi Rahayu (Universitas KH. Abdul Chalim Mojokerto, 2025)
Increased consumer awareness of environmental issues has driven a shift in preference and loyalty to environmentally friendly products. This research intends to investigate how green trust acts as a mediating factor in the link between green brand image and green products in relation to customer loyalty, particularly among Avoskin skincare users in Malang City. The methodology applied is quantitative, involving 186 participants chosen via non-probability sampling methods. The analysis of the data was carried out using the Structural Equation Modeling (SEM) technique through SmartPLS 4.0. The outcomes reveal that the green brand image and green product significantly influence both green trust and customer loyalty. Furthermore, it is confirmed that green trust serves as an important mediator in the impact of green brand image and green products on customer loyalty. These results highlight the critical nature of trust and enduring loyalty among environmentally conscious consumers. This research adds value to the establishment of sustainable marketing initiatives within Indonesia's skincare sector.